Structured Optical Materials Controlled by Light. Issue 15 (11th May 2018) - Nocentini, Sara; Martella, Daniele; Parmeggiani, Camilla; Zanotto, Simone; Wiersma, Diederik S.
Abstract: Materials whose optical response is determined by their structure are of much interest both for their fundamental properties and applications. Examples range from simple gratings to photonic crystals. Obtaining control over the optical properties is of crucial importance in this context, and it is often attempted by electro‐optical effect or by using magnetic fields. In this paper, the use of light is introduced to switch and tune the optical response of a structured material, exploiting a physical deformation induced by light itself. In this new strategy, light drives an elastic reshaping, which leads hence to a change in the optical response. This is made possible by using liquid crystalline networks structured by direct laser writing. As a proof of concept, a grating structure with sub‐millisecond time response is demonstrated for optical beam steering, exploiting an optically induced reversible shape change. Experimental observations are combined with finite‐element modeling in order to understand the actuation process dynamics, and to obtain information on how to tune the time and the power response of this technology. This optical beam steerer opens up full optical control of light in a broad range of structured optical materials. Abstract : A two‐dimensional elastic micrograting acts as a fully optically driven beam steerer. Liquid crystalline network structured by direct laser writing enables to switch and tune the optical response of a structured material exploiting a physical reversible deformation induced by light itself. The device is characterized in different environments revealing a large optical response at sub‐millisecond time scales.